Determination of Copper (Cu), Lead (Pb), Chromium (Cr), and Mercury (Hg) in soil samples taken from the Payatas controlled dumping facility - Cherdphong Seedao (2008)
The amount and forms of heavy metals (Cd, Cr, Pb, and Hg) were studied in soils sorrounding Payatas Controlled Dumping Facility in Quezon City, Metro Manila, Philippines. Samples were taken from two boreholes, one upstream of the facility and another downstream of the facility. The samples were analyzed to determine amount and forms of heavy metals along depth of the borehole that are in the study area by using Toxic Characteristic Leaching Procedure (TCLP), acid digestion (EPA 3050B), and Selective Sequential Extraction (SSE) analysis. Using TCLP to determine amount of heavy metals that can be released to the soil surrounding the dumpsite, the result shows the concentrations of heavy metals whether upstream or downstream are relatively low concentration (Hg ,<0.0001 mg/L, Cd , <0.004 mg/L, Cr <0.02 mg/L, and Pb <0.01 mg/L) and are actually lower that the standard provided by the hazardous waste standards set in the Philippines' DAO 36. The total amount of heavy metals was analyzed by using EPA 3050B. The total amount of heavy metals analyzed using acid digestion yielded the following results: At the upstream, the amounts of Hg concentrations are 30.83 mg/kg and 8.80 mg/kg at a soil depth of 0.55-5.81 m and 7.5-24 m, respectively. The average amount of Cd is 3.72 mg/kg while the average amount of Cr is 59.79 mg/kg and the average Pb concentration of Pb is 29.4 mg/kg at soil depth of 0.55-24 m. At the downstream, the amounts of Cd, Cr, Pb, and Hg are 4.86 mg/kg, 40.6 mg/kg, 29 mg/kg, and 9.62 mg/kg, respectively. The difference of the heavy metal content between the upstream and downstream holes is not significant. The samples from the downstream borehole were used to determine the following fractions of Pb and Cd: soluble exchangeable, surface adsorbed, organic mater, Mn oxides, poor crystalline Fe oxides, crystalline Fe oxides, and residual, by using SSE. The result shows that at the topmost layer, 62.67% of Pb is in the form of soluble-exchangeable fraction, while at 1.7 - 2 m depth, 64.41% of the Pb is in the form of Crystalline Fe oxides. For cadmium, at the topmost layer, 49.36% exist as residual fraction. At the layer from 2.7 - 3 m of soil, 65.79% is in the form of Mn oxides fraction.
"May 2008."
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Soils -- Heavy metal content; Sanitary landfills -- Philippines -- Payatas (Quezon City).; Waste disposal sites -- Philippines -- Payatas (Quezon City).